2003
DOI: 10.1128/jcm.41.1.373-378.2003
|View full text |Cite
|
Sign up to set email alerts
|

M Protein Gene Type Distribution among Group A Streptococcal Clinical Isolates Recovered in Mexico City, Mexico, from 1991 to 2000, and Durango, Mexico, from 1998 to 1999: Overlap with Type Distribution within the United States

Abstract: To examine the type distribution of pathogenic group A streptococcal (GAS) strains in Mexico, we determined the emm types of 423 GAS isolates collected from ill patients residing in Mexico (Durango or Mexico City). These included 282 throat isolates and 107 isolates from normally sterile sites. Of the other isolates, 38 were recovered from other miscellaneous infections. A total of 31 different emm types were found, revealing a broad overlap between commonly occurring emm types in Mexico and the United States.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
15
4

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(23 citation statements)
references
References 13 publications
4
15
4
Order By: Relevance
“…In contrast, emm type 28, followed by types 12, 81, 4, and 89, was the leading type among noninvasive cases. Finally, emm type 12 was the most prevalent type among noninvasive throat isolates, which is in agreement with previous findings [35].…”
Section: Discussionsupporting
confidence: 82%
“…In contrast, emm type 28, followed by types 12, 81, 4, and 89, was the leading type among noninvasive cases. Finally, emm type 12 was the most prevalent type among noninvasive throat isolates, which is in agreement with previous findings [35].…”
Section: Discussionsupporting
confidence: 82%
“…Our finding of emm12 to be common in throat isolates is in line with those previously reported [10,17,18]. Our finding of emm1 strains as a cause for pharyngitis is also commonly known, although emm1 is often considered to cause especially invasive disease [10,[17][18][19]. In our study material, emm77 was found especially in skin and wound swabs, but it was also the most common emm type in deep infection and blood isolates.…”
Section: Discussionsupporting
confidence: 93%
“…Our study shows that emm types identified among this population is vastly different from those reported other parts of the world (Hu et al 2002;Ho et al 2003;Gardiner et al 1998;Dicuonzo et al 2001;Espinosa et al 2003;Alberti et al 2003). Interestingly, it is also markedly different from those reported from other endemic regions such as Ethiopia (Tewodros and Kronvall 2005).…”
Section: Resultscontrasting
confidence: 75%